Multiple policies to enhance prescribing efficiency for established medicines in Europe with a particular focus on demand-side measures: findings and future implications - Godman, Brian; Wettermark, Bjorn; van Woerkom, Menno; Fraeyman, Jessica; Alvarez-Madrazo, Samantha; Berg, Christian; Bishop, Iain; Bucsics, Anna; Campbell, Stephen; Finlayson, Alexander E.; Fürst, Jurij; Garuoliene, Kristina; et al. (Frontiers in Pharmacology, 2014)
Introduction: The appreciable growth in pharmaceutical expenditure has resulted in multiple initiatives across Europe to lower generic prices and enhance their utilisation. However, considerable variation in their use and prices. Objective: Assess the influence of multiple supply and demand-side initiatives across Europe for established medicines to enhance prescribing efficiency before a decision to prescribe a particular medicine. Subsequently utilise the findings to suggest potential future initiatives that countries could consider. Method: Analysis of different methodologies involving cross national and single country retrospective observational studies on reimbursed use and expenditure of PPIs, statins and renin-angiotensin inhibitor drugs among European countries. Results: Nature and intensity of the various initiatives appreciably influenced prescribing behaviour and expenditure, e.g. multiple measures resulted in reimbursed expenditure for PPIs in Scotland in 2010 56% below 2001 levels despite a 3 fold increase in utilisation and in the Netherlands, PPI expenditure fell by 58% in 2010 vs. 2000 despite a 3-fold increase in utilisation. A similarly picture was seen with prescribing restrictions, i.e. (i) more aggressive follow-up of prescribing restrictions for patented statins and ARBs resulted in a greater reduction in the utilisation of patented statins in Austria vs. Norway and lower utilisation of patented ARBs vs. generic ACEIs in Croatia than Austria. However, limited impact of restrictions on esomeprazole in Norway with the first prescription or recommendation in hospital where restrictions do not apply. Similar findings when generic losartan became available in Western Europe. Conclusions: Multiple demand-side measures are needed to influence prescribing patterns. When combined with supply-side measures, activities can realise appreciable savings. Health authorities cannot rely on a ‘spill over’ effect between classes to affect changes in prescribing